2012
DOI: 10.1177/0884533611434116
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Supplementation in the Critically Ill

Abstract: Selenium (Se) is an essential trace element with antioxidant, immunological, and anti-inflammatory properties, which are attributed to its presence in selenoproteins, as the 21st amino acid selenocysteine. These selenoenzymes are involved in redox signaling, antioxidant defense, thyroid hormone metabolism, and immune responses. Dietary intakes differ considerably between geographical regions, due to variability of the Se food content, leading to differences in dietary reference intakes and toxicity cautions. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 95 publications
1
92
0
1
Order By: Relevance
“…It should be emphasized, however, that plasma selenium concentrations do not ultimately represent the amounts of tissue selenium, as there is only 0.2 mg selenium in plasma for 20 to 40 mg in the whole body [26]. Moreover, plasma selenium concentrations decrease during the acute-phase response, likely due to endothelial injury leading to transcapillary escape of selenium proteins [9,27]. Although reflecting short-term selenium status and responding rapidly to selenium supplementation, it may not accurately reflect tissue selenium content or seleno-enzyme activity in the presence of systemic inflammation [25,27].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It should be emphasized, however, that plasma selenium concentrations do not ultimately represent the amounts of tissue selenium, as there is only 0.2 mg selenium in plasma for 20 to 40 mg in the whole body [26]. Moreover, plasma selenium concentrations decrease during the acute-phase response, likely due to endothelial injury leading to transcapillary escape of selenium proteins [9,27]. Although reflecting short-term selenium status and responding rapidly to selenium supplementation, it may not accurately reflect tissue selenium content or seleno-enzyme activity in the presence of systemic inflammation [25,27].…”
Section: Discussionmentioning
confidence: 98%
“…In intensive care, the growing interest in studying the effect of selenium supplementation in critically ill adults stems from the evidence of the association between its deficiency and poor clinical outcome [7,8] and also from the beneficial role of selenium in immune and antioxidant systems. The reduction in circulating and tissue concentrations of antioxidant enzymes observed in these patients has been associated with disease severity, progression of organ dysfunction and mortality [7][8][9], which have favored its supplementation in certain specific situations [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The laboratory substudy of North American patients did not reveal the selenium deficiency consistently observed in European and South American trials of selenium status in critically ill and healthy persons. 16,17 These differences may reflect the considerable depletion of selenium in soil observed in parts of Europe but not throughout North America. 18 We may have prescribed an insufficient dose of selenium or used an ineffective dosing schedule, since a higher-thannormal level of selenium in the blood may be associated with the best outcome 19 and an initial bolus of selenium might have been more effective than the continuous administration we used.…”
Section: Discussionmentioning
confidence: 99%
“…The essential trace element selenium has antioxidant, anti-inflammatory and immunomodulatory effects 1 . Recent research has focussed on chronic dietary intakes and the potential role of selenium as a protective agent against some cancers, cardiac disease, fertility disorders, and cognitive decline 2 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%